CC5 A Case of Urticarial Vasculitis leading to HIV diagnosis. (30th June 2016) - Garner, Anna; Colton, Hayley; Ali, Rokiah; Cockayne, Sarah
Abstract : This abstract has been temporarily removed while important corrections are made.